Occurrence of soil-inhabiting entomopathogenic fungi within a conventional and organic farm and their virulence against Spodoptera litura - AMINUDIN AFANDHI; FERY ABDUL CHOLIQ; ITO FERNANDO; YOSEP MINAR ALBERT NANDUS MARPAUNG; YOGO SETIAWAN (Society for Indonesian Biodiversity, 2022)
Abstract. Afandhi A, Choliq FA, Fernando I, Marpaung YMAN, Setiawan Y. 2022. Occurrence of soil-inhabiting entomopathogenic fungi within a conventional and organic farm and their virulence against Spodoptera litura. Biodiversitas 23: 1172-1180. Naturally occurring entomopathogenic fungi (EPF) are important components in agroecosystems as they serve as biocontrol agents of insect and mite pests. However, some cultivation practices may have deleterious effects on EPF. In this study, the occurrence of soil-inhabiting EPF was investigated between a conventional and organic farm. EPF was baited using Tenebrio molitor larvae, and their virulence was tested against Spodoptera litura larvae. The results showed a higher occurrence of EPF in the organic farm than the conventional farm, with Aspergillus sp., Beauveria sp., and Gliocladium sp. were exclusively found in organic soils. Among the twenty-five EPF isolates obtained, only four isolates were avirulent against S. litura larvae. Isolates belonging to Beauveria, Metarhizium, and Paecilomyces genera caused high mortality of S. litura larvae ranging from 40 to 65%. There was a significant positive relationship between the conidial viability of EPF and larval mortality. Since virulent isolates were found in conventional soils, efforts in preserving EPF prevalence are needed through the implementation of appropriate cultivation practices. The synthetic agrochemicals exclusion, organic fertilizers application, and crop rotation practiced in the organic farm should be integrated into any other agroecosystems as a form of conservation biological control strategies to strengthen the pest control service provided by EPF.